Implementation of Concept Mapping As Learning Strategy to Improve Social Science Learning Outcomes in The Theme of Wonderful Diversity In My Country to The Fourth Grade Students of SDN 2 Prembun In Academic Year of 2019/2020 - Retno Novianti Rahayu; Wahyudi Wahyudi; Joharman Joharman (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The objectives of the research were: (1) to describe the steps in the implementation of concept mapping as learning strategy, (2) to improve social science learning outcomes in the theme of wonderful diversity in my country, and (3) to describe the obstacles and solutions in the implementation of concept mapping as learning strategy.The research was a collaborative classroom action research. The types of data were qualitative data and quantitative data. Data collection techniques included observation, interviews, and tests.The results of the research indicated that: (1) the steps in the implementation of concept mapping as learning strategy were: a) the teacher explained concept mapping as learning strategies to the students, b) the students worked in small groups, c) the students expressed the ideas, d) the students determined the main concepts, e) the teacher guided the students to create concept maps, f) the students presented the results of the discussion, g) the teacher provided feedback, h) the students summarized the lesson, i) the students made evaluation; (2) the implementation of the concept mapping as learning strategy improved students’ learning outcomes, (3) the obstacle was some students disturbed other groups during group discussions. The solution to overcome the obstacle was the teacher walked over to the students and gave a reprimand.